1995
DOI: 10.1520/jfs13816j
|View full text |Cite
|
Sign up to set email alerts
|

Fatality Due to Gamma-Hydroxybutyric Acid (GHB) and Heroin Intoxication

Abstract: The first case of fatal intoxication due to ingestion of gamma-hydroxybutyric acid (GHB) and intravenous use of heroin is reported. A 42-year-old man, known to have been a heroin addict and to have taken other psychoactive substances, who had been in treatment with GHB for several months, was found dead. Anatomohistopathologic examination showed generalized visceral congestion, edema and pulmonary anthracosis, chronic bronchitis and chronic active hepatitis. Toxicological findings included fluid and tissue dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 21 publications
1
36
0
2
Order By: Relevance
“…Therefore, the presence of such substances in deaths involving GHB should be taken into consideration when assessing fatalities attributed to GHB intoxication (Kugelberg et al, 2010;Snead and Gibson, 2005). Ferrara et al (1995) reported a death involving GHB and heroin (diacetylmorphine), a high concentration of morphine was detected in the blood (770 mg/L). In five other reported GHB deaths, ethanol has also been involved at significant concentrations (Davis, 1999;Elliott, 2000Elliott, , 2001.…”
Section: Fatalitiesmentioning
confidence: 99%
“…Therefore, the presence of such substances in deaths involving GHB should be taken into consideration when assessing fatalities attributed to GHB intoxication (Kugelberg et al, 2010;Snead and Gibson, 2005). Ferrara et al (1995) reported a death involving GHB and heroin (diacetylmorphine), a high concentration of morphine was detected in the blood (770 mg/L). In five other reported GHB deaths, ethanol has also been involved at significant concentrations (Davis, 1999;Elliott, 2000Elliott, , 2001.…”
Section: Fatalitiesmentioning
confidence: 99%
“…Physical dependence was reported in one source. 15 Gamma hydroxybutyrate is known to act synergistically with alcohol, benzodiazepines, narcotics, and other neuroleptic medications to produce central nervous system and respiratory depression. 6 • 7 This case is the first report of chronic high-dose abuse with withdrawal syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…After oral administration, it is rapidly absorbed within 10-15 min. It has a very short elimination half-life of about 27 min [8]. Both oral absorption and elimination are capacity limited.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…An increased number of outbreaks of coma associated with seizures induced by the illicit use of GHB has been reported in the United States [4], Britain [5] and Australia. Recently, deaths due to the ingestion of GHB have been reported [6,8]. This review aims to alert physicians to the increasing use of GHB among youths and to consider GHB poisoning in the differential diagnosis in patients presenting with coma and myoclonic seizures.…”
mentioning
confidence: 99%